The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1111/j.1365-2567.2008.02942.x
|View full text |Cite
|
Sign up to set email alerts
|

A component of polysaccharide peptidoglycan complex on Lactobacillus induced an improvement of murine model of inflammatory bowel disease and colitis‐associated cancer

Abstract: SummaryInterleukin-6 (IL-6)/signal transducer and activator of transcription 3 (STAT3) signals play key roles in the pathogenesis of inflammatory bowel disease (IBD). We previously described that both intact cells and a cell wall-derived polysaccharide-peptidoglycan complex (PSPG) in a strain of lactobacillus [Lactobacillus casei Shirota (LcS)] inhibited IL-6 production in lipopolysaccharide (LPS)-stimulated lamina propria mononuclear cells (LPMCs) isolated from murine IBD. Diets with LcS improve murine IBD by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(65 citation statements)
references
References 48 publications
2
58
0
5
Order By: Relevance
“…These themes are consistent with previous research of polysaccharide effects. For example, the reports of perceived change in gastrointestinal health are consistent with mechanistic studies in animals that demonstrate positive effects of polysaccharide intake on gut function (Marzorati, et al, 2010;Matsumoto, et al, 2008). Similarly, the reports of perceived improvement in the experience of arthritic pain lend support to the findings of saccharide involvement in arthritic conditions (A.…”
Section: Discussionsupporting
confidence: 71%
“…These themes are consistent with previous research of polysaccharide effects. For example, the reports of perceived change in gastrointestinal health are consistent with mechanistic studies in animals that demonstrate positive effects of polysaccharide intake on gut function (Marzorati, et al, 2010;Matsumoto, et al, 2008). Similarly, the reports of perceived improvement in the experience of arthritic pain lend support to the findings of saccharide involvement in arthritic conditions (A.…”
Section: Discussionsupporting
confidence: 71%
“…While the bacterium is known to be a strong Th1-type cytokine inducer (32), of which the active component was proposed to be LTA (12), it exerts anti-inflammatory activity against diabetes mellitus (26) and inflammatory bowel disease (24,25) in animal models. It was shown that the cell wall preparation containing PS and PG could be the active component of the anti-inflammatory activity (25). We have focused on the role of cell wall PSs in the immune modulation activities of YIT 9029 and have found that high-molecular-mass cell wall PSs (PS-1) are a prerequisite for anti-inflammatory activity (43).…”
mentioning
confidence: 99%
“…Based on these properties of the Lactobacillaceae group, Glendinning et al [26] hypothesized the existence of a symbiotic relationship between the helminths and the microbes to be one of the key players in reducing intestinal inflammation. Matsumoto et al [27] has also documented the anti-inflammatory properties of some members of the genus Lactobacillus. The exact effects on the gut microbiota as a result of this cascade of reaction have not been investigated in details [5].…”
Section: Role Of the Gut Microbiota In Establishment Of The Helminth mentioning
confidence: 99%